1967
DOI: 10.1029/jz072i024p06335
|View full text |Cite
|
Sign up to set email alerts
|

Geomagnetic depth sounding and upper mantle structure in the Cordillera region of western North America

Abstract: This report describes recent geomagnetic depth-sounding investigations on the inland (Cordillera) anomaly first reported by Schmucker at latitude 32øN. It includes Hyndman's profile at latitude 49.5øN and two subsequent profiles at latitudes 35øN and 51øN. All three profiles crossed the transition between the 'high-/' and 'low-/' zones. Characteristic parameters have been derived from power spectral analysis of the data. The attenuation in the normalized vertical component at the western stations increases wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

1967
1967
1983
1983

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(13 citation statements)
references
References 22 publications
1
11
1
Order By: Relevance
“…At latitude 32N the change in heat flow (from 1.1kcal/cm2 sec in the Texas Foreland to a mean of 2.21+0.43 in the Basin and Range Province) occurs in close agreement with the location of the GDS discontinuity (Warren et al, 1969). At latitude 35N the relation is not clear; Caner et al (1967) inferred an eastward swing of the GDS discontinuity, which is not in agreement with the heat-flow data. However, Porath (1969) indicated that the eastwards persistence of the low-Z zone at this latitude could be interpreted by a separate (shallow) anomaly rather than a swing in the main "western-type" conductivity structure; Caneret al (1970) have shown that such a reinterpretation of the original data is possible (since no MT "calibration" is available at this latitude, profile -type GDS data are necessarily ambiguous).…”
Section: Heat Flowcontrasting
confidence: 33%
“…At latitude 32N the change in heat flow (from 1.1kcal/cm2 sec in the Texas Foreland to a mean of 2.21+0.43 in the Basin and Range Province) occurs in close agreement with the location of the GDS discontinuity (Warren et al, 1969). At latitude 35N the relation is not clear; Caner et al (1967) inferred an eastward swing of the GDS discontinuity, which is not in agreement with the heat-flow data. However, Porath (1969) indicated that the eastwards persistence of the low-Z zone at this latitude could be interpreted by a separate (shallow) anomaly rather than a swing in the main "western-type" conductivity structure; Caneret al (1970) have shown that such a reinterpretation of the original data is possible (since no MT "calibration" is available at this latitude, profile -type GDS data are necessarily ambiguous).…”
Section: Heat Flowcontrasting
confidence: 33%
“…Caner, Cannon & Livingstone (1967) carried out geomagnetic deep sounding along a profile across northern New Mexico into Oklahoma and found high 2 only at their eastern-most station in western Oklahoma. They suggest that the anomaly related to the eastern front of the Rockies swings towards the east in northern New Mexico and does not follow the topographic front of the Rocky Mountains.…”
Section: Previous Work and Description Of Arraymentioning
confidence: 99%
“…This geophysical work suggests therefore that the edge of the craton lies west of the Rocky Mountains rather than along the line of King drawn in Fig. 1 To the south in the United States, data from Schmucker (1964), Caner et al (1967), Camfield et al (1971, and Porath and Gough (1971) have been used to derive the I values shown on Fig. 1.…”
Section: Data Presentationmentioning
confidence: 97%